Miriko [Nagahama] and Harry Murakami with Their Family at Harry's Retirement Party, June 23, 1985 (1985)
Inscription on back of photograph: "Harry's Murakami Retirement Celebration. June 23, 1985. West L.A. United Methodist Church. Left to right Gary + Peggy* Young, Alan* + Ilene Murakami, Harry + Miri (Nagahama), Gail*, Lowel + Ann* Zweigle, Glenn + Karen* Murakami. Front row Justin Young (3), Connie Zweigle (4). *Harry's + Miri's Offspring."